PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG TERIGU GUNA MEMINIMALKAN BIAYA DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN METODE JUST IN TIME (JIT) PADA PERUSAHAAN MIE TENAGA MUDA PEKANBARU - Indriyani, Romauli; Restu, Restu; Anggia, Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the optimal quantity of wheat flour as raw material purchased and the total amount of Inventory Costs of wheat flour at Perusahaan Mie Tenaga Muda by comparing two methods at once, namely by using the Economic Order Quantity (EOQ) method and the Just In Time method (JIT). The type of research method used is a descriptive study with quantitative approach. The source of data in this study is a primary data, which obtained directly from interviews and documents from the company. The data analysis used in this study is using EOQ and JIT methods. The results of this study prove that by applying the JIT method there is a greater difference in savings compared to the EOQ method. In a comparison of these two methods, the results show that the JIT method has greater amount in saving of Inventory Costs for 5 years in 2015 - 2019, respectively Rp. 2,311,558.9; Rp. 2,491,383.59; Rp. 2,669,765.48; Rp. 3,040,025.75; Rp. 3,612,489.78. Based on the results of study, it is advisable for Perusahaan Mie Tenaga Muda to apply the JIT method in order to minimize the inventory costs.Keywords: Raw Material Inventory, Total Inventory Cost, Economic Order Quantity, Just In Time.